Occupational structure and local dynamics: A test of convergence among Italian provinces - Tomaso Pompili (European Regional Science Association (ERSA), 1998)
Labour force quality (human capital endowment) is crucial to the goal of maximum long run prosperity, be it applied to firms and production systems or to cities and urban systems. The aim of this paper is to highlight the significant explanatory role of human capital in local economic development and in its spatial differentials, with reference to endogenous growth theory. After a synthetic review of the literature on these issues and a presentation of data and method, a regression analysis tests the hypotheses of absolute convergence (of income per capita / product per job) and of convergence conditional to the occupational structure of the labour force, as an appropriate proxy of human capital. The test is based on the 90+ Italian provinces during the 1960s, 1970s and 1980s. Original features include the choice of the proxy for human capital, but also of the spatial detail and of the twin dependent variables. Results support the absolute convergence hypothesis, but also show the explanatory value of disaggregated human capital (occupational structure), whereas the aggregated hypotheses of dualism and development stages can be rejected; finally a (static) production function approach with disaggregated human capital obtains excellent results.
Keywords: 330